Respuesta :
Answer:
=6(1 + c)
Step-by-step explanation:
Given that:
= -2/3(12c-9)+14c
By simplifying:
Negative sign before bracket will alter the inner signs
=-24c/3 + 18/3 +14c
= -8c + 6 + 14c
= 6 + 6c
By taking 6 common:
=6(1 + c)
I hope it will help you!
Answer:
6(c + 1)
Step-by-step explanation:
Given: [tex]$ - \frac{2}{3} (\ 12c - 9 )\ + 14c $[/tex].
Distributing [tex]$ - \frac{2}{3}$[/tex] over [tex]$ 12c - 9 $[/tex] we get:
[tex]$ - \frac{2}{3} (12c) + \frac{2}{3} (9) + 14c $[/tex].
On simplifying we get: [tex]$ -2(4c) + 2(3) + 14c $[/tex]
[tex]$ \implies -8c + 6 + 14c = 6c + 6 = 6(c + 1) $[/tex]
Therefore the answer is [tex]$ 6(c + 1) $[/tex].